2012
DOI: 10.5505/tjtes.2012.01047
|View full text |Cite
|
Sign up to set email alerts
|

Presence of accompanying head injury in patients with maxillofacial trauma

Abstract: AMAÇMaksillofasiyal kırığı bulunan hastalar, bu travmaya eşlik eden kafa travması geçirme konusunda yüksek risk altın-dadırlar. Bu hastalarda kafa travmasının erken anlaşılma-sı hastanın sağkalımı ve iyileşmesi için kritik öneme sahiptir. GEREÇ VE YÖNTEMOcak 2006 ile Eylül 2009 tarihleri arasında hastanemizin acil servisine maksillofasiyal kırık nedeniyle gönderilen 246 hastanın kayıtları geriye dönük olarak tarandı. Hastaların yaş, cinsiyet, maksillofasiyal travmanın nedeni, tipi, yerleşimi ve kafa travması a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
21
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 24 publications
12
21
3
5
Order By: Relevance
“…Isik et al. also found a significant increase in the risk of concomitant THI only in patients aged 41–60 years . The result of our study was identical with their studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Isik et al. also found a significant increase in the risk of concomitant THI only in patients aged 41–60 years . The result of our study was identical with their studies.…”
Section: Discussionsupporting
confidence: 91%
“…The 8.6% incidence of THI in our population is slightly lower than the majority of the findings in previous studies . However, Lim et al.…”
Section: Discussioncontrasting
confidence: 71%
“…The male predominance in our study agrees with what is reported in the literature. 1,[6][7][8][9] The male to female ratio of 9:1 was comparable to other studies. 10,11 Males are at a greater risk of crashes and maxillofacial injuries because of the increased use of vehicles and travel compared to females.…”
Section: Discussionsupporting
confidence: 73%
“…7 Studies which quote a lesser incidence of malocclusion have accepted open reduction and internal fixation as a gold standard of treatment. 9,24 Secondary wound infection was 4% in our study, comparable to the study by Ahmed et al (5.6%) who also emphasized the need for prophylactic antibiotics. 25 Studies by…”
Section: Pajtsupporting
confidence: 79%
See 1 more Smart Citation